Postanesthetic Severe Oral Angioedema in Patient’s Taking Angiotensin-Converting Enzyme Inhibitor - Acílio Marques; Carla Retroz-Marques; Sara Mota; Raquel Cabral; Matos Campos (Case Reports in Anesthesiology)
Angiotensin-converting enzyme (ACE) inhibitors are the leading cause of a drug-induced angioedema. This occurrence is frequently underdiagnosed, but its relapse can be life-threatening. The authors’ intention in reporting this clinical case is to sound a warning about reviewing attitudes and surveillance to try to improve patient perioperative safety.